Dynamics in the molluscum contaminant microflora Aulacomya ater choro and processed raw ceviche. 1 - Quantitative analysis. - Coha, Juana María (1974)
We have determined quantitatively Coliforms and Enterococcus in the mollusk Aulacomya ater "choro", as an index of human enteric contamination during the preparing process of "cebiche". There have been processed 1152 specimens from Lima and Callao markets. The highest average of contamination for both microbial groups, in choros uncooked (part a), from markets situated in places with little hygiene' conditions and more population. The environmental temperature in summer’ months show us an increscent of this kind of microbial organisms. The temperature of cooking from specimens before preparing “cebiche” (part b), gets to kill all the microbial forms, reappearing Coliforms (part c), as a result of the addition of condiments. The lemon juice did not actuate as effective bactericidal.